Serum rapidly stimulates ouabain-sensitive 86-RB+ influx in quiescent 3T3 cells. - Rozengurt, E (1975)
Serum causes a 4-fold increase in 86Rb+ (a K+ tracer) influx in quiescent 3T3 mouse fibroblast cells. It is one of the earliest changes caused by serum, being seen in 2 min and reaching a maximum in 10 min. Removal of serum causes rapid reversal of this effect. Serum acts mainly by increasing the maximum velocity, Vmax, of entry. Ouabain inhibits entry of 86Rb+ (82-90%) both in the presence and absence of serum, but does not alter exit. The rapid increase in cation influx is unaffected by cycloheximide and by changes in cyclic AMP and GMP. Low concentrations of insulin, epidermal growth factor, and prostaglandins (E1 and F2alpha) produced a smaller (80%) activation of 86Rb+ entry. Ouabain, at a level that inhibits cation influx, also prevents the onset of DNA synthesis following serum addition; this is reversible effect dependent on the concentration of K+ in the medium. This suggests that cation pumping activity may be required for initiation of DNA synthesis.